Prevention and treatment of thrombosis in cancer and oncohematological patients - O. V. Somonova; A. L. Elizarova; T. V. Davydova (Онкогематология)
The purpose of the review is to highlight the current possibilities for the prevention and treatment of venous thrombotic complications in patients with cancer.The data of 52 scientific sources published in the Russian and foreign press in 1997–2020 are considered.Cancer patients are at high risk of thrombotic complications, which worsen the outcome of anticancer treatment and are one of the leading causes of death. Thrombosis in an oncological patient increases the risk of death by 30 times, which is associated with fatal thromboembolism and a more aggressive course of the disease. The leading role in the pathogenesis of thrombotic complications is played by disorders in the hemostasis system caused both by the tumor itself and by therapy. Low molecular weight heparins are considered the basis for specific prophylaxis of thromboembolic complications in cancer patients. The use of low molecular weight heparins after surgery and during chemotherapy effectively reduces the incidence of venous thrombosis. Direct oral anticoagulants are promising drugs for oral administration and are indicated as one of the treatment options for patients with tumor-associated thrombosis with a low risk of bleeding and no drug interactions with ongoing systemic chemotherapy.